2010
DOI: 10.1007/s11661-010-0335-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Corrosion Cracking of AISI 4340 Steel in Aqueous Environments

Abstract: Stress corrosion cracking of the high-strength martensitic steel AISI 4340 (yield stress = 1503 MPa) in NaCl aqueous solutions of different concentrations was studied experimentally using compact tension specimens in free corroding conditions. The experiments were conducted under the controls of constant load, constant crack opening displacement (COD), constant loading rate, and constant COD rate. Despite the differences in controlling conditions, the experiments yielded similar results for the threshold stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The da/dN vs. ΔK relationship generated at constant σ max of 300 MPa and R of 0.5 for humid N 2 and full immersion in 0.0006, 0.006, 0.06, 0.6, and 1.5 M NaCl solutions polarized to -200 mVsce, are reported in Figure 3. While testing was also completed in deionized (DI) water and 3M NaCl solutions, these data are not reported due to the onset of an time dependent intergranular (IG) fracture process, attributed to an SCC cracking mode exacerbated by cyclic loading [18,[90][91][92][93][94]. The onset of SCC for the DI water conditions is not fully understood and a full investigation is outside of the scope of the current effort, however, such behavior is not unprecedented [77] and an inhibiting effect of low [Cl -] concentrations in acid solutions has been reported [95].…”
Section: Long Crack Growth Ratesmentioning
confidence: 99%
“…The da/dN vs. ΔK relationship generated at constant σ max of 300 MPa and R of 0.5 for humid N 2 and full immersion in 0.0006, 0.006, 0.06, 0.6, and 1.5 M NaCl solutions polarized to -200 mVsce, are reported in Figure 3. While testing was also completed in deionized (DI) water and 3M NaCl solutions, these data are not reported due to the onset of an time dependent intergranular (IG) fracture process, attributed to an SCC cracking mode exacerbated by cyclic loading [18,[90][91][92][93][94]. The onset of SCC for the DI water conditions is not fully understood and a full investigation is outside of the scope of the current effort, however, such behavior is not unprecedented [77] and an inhibiting effect of low [Cl -] concentrations in acid solutions has been reported [95].…”
Section: Long Crack Growth Ratesmentioning
confidence: 99%
“…This seemingly anomalous behavior in ostensibly less severe DI water is consistent with prior findings of enhanced SCC in pure water and low chloride concentrations. 38,39 Researchers postulate that this behavior could correlate to extrinsic toughening due to local branching in the higher chloride conditions; however, this argument is not fully satisfying. 39 Detailed investigation of the mechanistic cause of this behavior is outside the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 9 it was confirmed that the highest values of d /dt were reached in deaerated distilled water; when oxygen or Cl − existed, the crack growth rate within the plateau region decreased. It should be noticed that in deaerated distilled water the SCC growth curve was different from the curves in other aqueous solution by the absence of the pronounced plateau in stage II; this fact indicated that in deaerated distilled water the velocity of crack extension was dependent on the stress intensity in all three stages of crack growth; similar researches could observe the same phenomenon [15,18], while when oxygen or Cl − existed the pronounced plateau of stage II existed. From Figure 9 ISCC four kinds of aqueous solution could be confirmed, and deaerated distilled water ISCC of 4340 was about 11MPa⋅m 1/2 , which was almost equal to the value of ISCC in 0.1mol/l chloride aqueous solution; oxygencontaining distilled water ISCC decreased, and the value was about 10MPa⋅m 1/2 ; when both oxygen and chloride existed, ISCC decreased to 9MPa⋅m 1/2 furtherly [5,15].…”
Section: Crack Propagation Of 4340 Steel Under Different Aqueousmentioning
confidence: 87%
“…Once crack is initiated, the stress concentration in the crack tip would aggravate the process above and increase the crack propagation [20], until brittle rupture occurred. Chloride induced brittle rupture had been discussed in many reference [15,18], when both oxygen and chloride existed, the chloride would induce both corrosion and oxidization of freshly exposed metal repeatedly and further increase the crack propagation.…”
Section: Analysis On the Corrosion Morphology Of 4340 Duringmentioning
confidence: 99%
See 1 more Smart Citation